A coumarin/cyanoacetamide-derived lysosome-targeting probe for detecting bisulfite and viscosity changes in living cells and zebrafish. (December 2022) - Zhang, Ling; Wu, Wei-Na; Zhao, Xiao-Lei; Fan, Yun-Chang; Wang, Yuan; Xu, Zhi-Hong
Abstract: A coumarin/cyanoacetamide-based probe was produced by a simple condensation reaction. The probe exhibits high selectivity towards bisulfite (HSO3 − ) and viscosity changes based on either fluorescence or UV–Vis spectra in almost pure aqueous media. The addition of HSO3 − induced a significant blue shift in the emission maximum of the free probe (from 575 nm to 485 nm) with a short response time (5 min), a broad function pH range (3.0–11.0), and a low detection limit (74 nM), via the recognition mechanism of bisulfite-involved Michael addition reaction. In parallel, the fluorescence intensity at 575 nm of the probe increased significantly along the increasing viscosity of the test media owing to the prohibited rotation of CC bridged rotors in probe 1 . Notably, the probe could monitor the level of lysosomal HSO3 − and viscosity changes in HeLa cells and zebrafish. Graphical abstract: Image 1 Highlights: A coumarin/cyanoacetamide-based fluorescence probe with lysosome-targeting has been developed. The probe can detect bisulfite (HSO3 − ) and viscosity with high selectivity and sensitivity based on either fluorescence or UV–Vis spectra in almost pure aqueous media. The probe has been successfully applied to the imaging of endogenous and exogenous HSO3 − and viscosity changes in the lysosomes of living cells and zebrafish.